Internal medicine resident education improves cardiac rehabilitation knowledge, attitudes, and referral rates: A pilot study - Maggie Wang; Nare Torosyan; C. Noel Bairey-Merz; Janet Wei; Chrisandra L. Shufelt (Elsevier, 2022)
Background: Referrals to cardiac rehabilitation (CR) remain low despite evidence showing reduction in cardiovascular mortality and hospital readmissions. Resident education and awareness may be an opportunity to address barriers to CR referrals. Methods: This pilot study involves 20 internal medicine residents rotating at an ambulatory primary care clinic. Voluntary surveys were sent through an online-based survey platform. Following survey completion, residents received a 10-minute scripted lecture and an educational handout outlining CR components, availability, indications, insurance eligibility criteria, and referral process. Surveys were redistributed 2 months post-education to assess changes in mean aggregate knowledge scores and attitude ratings on a 5-point Likert scale. CR referral rates of eligible patients pre- and post-education were obtained through review of electronic medical records. Results: Sixteen (80%) residents completed both pre and post surveys, and 13 (81%) reported no education on CR in the prior year. There was a significant increase in mean aggregate knowledge scores on CR components (5.1 versus 7.0, P = 0.001), insurance coverage (2.4 versus 5.6, P< 0.001), and eligible diagnoses (7.1 versus 9.9, P = 0.03) following education. Attitudes towards CR also improved following education, particularly in self-reported comfort level with explaining CR to patients (3.69 versus 2.06, P<0.001) and perceived familiarity with CR referral process (4.00 versus 2.18, P<0.001). CR referrals increased from 0% (0 out of 10 eligible patients) to 33% (3 out of 9 eligible patients) over a 2-month period before and after education, respectively (P = 0.09). Conclusions: Internal medicine resident knowledge and attitudes towards CR significantly improved after formal education. Although there was a modest increase in the rates of CR referrals following resident education, this pilot study was not powered to detect statistical significance.